A Studi Keekonomian Pengembangan Lapangan Gas NE Menggunakan PSC Cost Recovery dan Gross Split: Economic Study of NE Gas Field Development Using Cost Recovery and Gross Split PSCs - Eka Saputra, Nanda; Hadziqul Abror; Riska Laksmita Sari (JSED, 2025)
The NE Field is one of the fields that has produced gas since 1970 and was not developed again after that due to certain reasons. Currently, the NE Field will be developed again to support production results to achieve the national targets that have been announced. In the development of oil and gas fields, several analyzes are needed both technically and economically. In this study, before carrying out economic analysis, the things that were carried out were a review of potential reserves and estimates of NE field development. using the volumetric method, the total reserves for the NE Field were obtained at 274.32 BCF and after calculating the Recovery Factor, the Remaining Reserve was obtained at 215.46 BCF, then determining deliverability to predict production in order to achieve the target plateau rate that had been agreed upon according to the contract and by simulating 6 wells. obtained a plateau rate of 19.74 MMscf after deducting CO2 with cumulative gas production of 129 BCF and a Recovery Factor of 67%. After obtaining production, an economic analysis was carried out and it was found that PSC Cost Recovery was more profitable for the contractor with NPV results (US$ M) 87,310.06, IRR 46%, and POT 3.41 years for PSC Cost Recovery while for PSC Gross Split the NPV results were ( US$M) 69,323.11, IRR 28%, and POT 6.27 years. And in terms of sensitivity, PSC Gross Split is more sensitive than PSC Cost Recovery.